2010
DOI: 10.1002/lary.20977
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomographic analysis of frontal recess anatomy and its effect on the development of frontal sinusitis

Abstract: The frequency of frontal recess cells analyzed in Taiwanese adult patients was similar to that analyzed in other Asian adult populations (Chinese and Korean). The frontoethmoid cells posterior and posterolateral to the frontal recess (suprabullar cells, frontal bullar cells, and supraorbital ethmoid cells) might reveal a more significant association with the development of frontal sinusitis than those anterior to the frontal recess (agger nasi cells, frontal cell types 1-3). The presence of supraorbital ethmoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 16 publications
0
60
0
1
Order By: Relevance
“…Our findings may not be directly applicable to patient populations with chronic frontal sinusitis, as it has been suggested that patients with chronic frontal sinusitis may have a higher prevalence of certain frontal cells that may predispose the frontal sinus to obstruction . Furthermore, adults who have had significant sinusitis during childhood and adolescence may have more limited development of the frontal recess cells compared with a nondiseased cohort …”
Section: Discussionmentioning
confidence: 65%
“…Our findings may not be directly applicable to patient populations with chronic frontal sinusitis, as it has been suggested that patients with chronic frontal sinusitis may have a higher prevalence of certain frontal cells that may predispose the frontal sinus to obstruction . Furthermore, adults who have had significant sinusitis during childhood and adolescence may have more limited development of the frontal recess cells compared with a nondiseased cohort …”
Section: Discussionmentioning
confidence: 65%
“…[460][461][462] In 2 studies of patients with a history of CRS, the presence of frontal recess cells and agger nasi cells were not associated with a higher incidence of frontal sinusitis. 462,463 Additionally, no association was found by DelGaudio et al 463 between frontal sinusitis and size of the frontal recess.…”
Section: S63mentioning
confidence: 96%
“…When specifically studying frontal sinus anatomy, DeConde et al 464 showed that the frontal sinus outflow dimensions, presence of an intersinus septal cell, and an anterior ethmoid artery on the mesentery did not impact QoL gains from endoscopic frontal sinus surgery. However, Lien et al 461 demonstrated an increased incidence of frontal sinusitis in cells that affect the posterior or posterolateral aspect of the frontal recess (suprabullar, supraorbital, and frontal bullar cells) with no association found with type 1-4 frontal cells. Langille et al 465 showed a significant relationship between the presence of frontal cells and mucosal thickening on CT imaging.…”
Section: S63mentioning
confidence: 99%
“…For those patients with frontal sinus disease, there are some anatomic abnormalities that can contribute to persistent blockage. Although many patients have agger nasi cells [23,24], which help to define the frontal sinus drainage pathway, others have cells that may block drainage. These 'frontal cells', as they have been called, may extend into the frontal sinus proper leading to constriction of frontal sinus drainage [25 & ].…”
Section: Key Pointsmentioning
confidence: 99%